F1 Q-COG – a cognitive assessment battery for huntington's disease. (13th September 2016) - Schubert, Robin; Weber, Nathalia; Reilmann, Ralf
Abstract : Background: The Repair-HD project is a EUFP 7 funded project, aiming to provide a protocol for stem cell therapy in Huntington's disease. As part of the clinical assessment protocol to track slow longitudinal progression in small HD patient cohorts, the "Q-Cog" assessment battery is conducted. The Q-Motor system applies sensitive force transducers and 3 d position tracking systems, to quantitatively measure motor function. Q-Cog assessments deploy the technology used in the Q-Motor system to benefit from the high accuracy of the sensors in tasks with high cognitive load. Aims: Primary objective is to establish an assessment battery with highly sensitive and robust endpoints, to track cognitive decline in small patient cohorts. Secondary objective is the development of a generic software for administration of Q-Cog and Q-Motor tasks in multicentric clinical trials. Methods: Subjects – We intend to include 30 HD subjects (CAG ≥ 36, age ≥ 18 yrs, TFC staging I or II) and 30 control subjects. Force Matching – The patient is asked to match a visually presented force by applying pressure on the force transducer. In a blinded variation, the patient is asked to reproduce presented force by memory (without visual feedback). Trail Making – Classic Trail Making test on paper but with Polhemus Stylus (6-axis position sensor). The patient is asked to connect-the-dots of 25 trail nodes on a paper labelled 1 to 25 (test A) or alternating a digit and a letter. Spiral Drawing – The patient is asked to retrace a spiral on a piece of paper with Polhemus Stylus (6-axis position sensor). Morse Code Mimicry – The patient is asked to tap a presented morse(-like) acoustical code on a force transducer. Results: The study piloting the Q-Cog assessment battery in Repair-HD has been launched. We report sample recordings and feasibility for the assessment battery in test subjects. Conclusions: The Q-Cog battery is applicable in HD patients and the novel software (currently in beta status) is applicable in multi-site settings.